Rosmarinic Acid Turned α-syn Oligomers into Non-Toxic Species Preserving Microtubules in Raw 264.7 Cells - Melo-Hurtado, F; Caballero-Alvial, L (Academic Press, 2024)
Parkinson s disease (PD) is the second most prevalent neurodegenerative disorder worldwide, and the therapeutic is focused on several approaches including the inhibition of fibril formation by small compounds, avoiding the formation of cytotoxic oligomers. Thus, we decided to explore the capacity of compounds carrying catechol moieties to inhibit the progression of α-synuclein. Overall, the compounds rosmarinic acid (1), carnosic acid (2), carnosol (3), epiisorosmanol (4), and rosmanol (5) avoid the progression of fibril formation assessed by Thiofavine T (ThT), and atomic force microscopy images showed that morphology is influenced for the actions of compounds over fibrillization. Moreover, ITC experiments showed a Kd varying from 28 to 51 µM, the ΔG showed that the reaction between compounds and α-syn is spontaneous, and ΔH is associated with an exothermic reaction, suggesting the interactions of hydrogen bonds among compounds and α-syn. Docking experiments reinforce this idea showing the intermolecular interactions are mostly hydrogen bonding within the sites 2, 9, and 3/13 of α-synuclein, and compounds 1 and 5. Thus, compound 1, rosmarinic acid, interestingly interacts better with site 9 through catechol and Lysines. In cultured Raw 264. 7 cells, the presence of compounds showed that most of them can promote cell differentiation, especially rosmarinic acid, and rosmanol, both preserving tubulin cytoskeleton. However, once we evaluated whether or not the aggregates pre-treated with compounds could prevent the disruption of microtubules of Raw 264.7 cells, only pre-treated aggregates with rosmarinic acid prevented the disruption of the cytoskeleton. Altogether, we showed that especially rosmarinic acid not only inhibits α-syn but stabilizes the remaining aggregates turning them into not-toxic to Raw 264.7 cells suggesting a main role in cell survival and antigen processing in response to external α-syn aggregates. © 2024